Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/atmos11030295
|View full text |Cite
|
Sign up to set email alerts
|

O3 Sensitivity and Contributions of Different NMHC Sources in O3 Formation at Urban and Suburban Sites in Shanghai

Abstract: Ground-level ozone (O3) pollution is still one of the priorities and challenges for air pollution control in the Yangtze River Delta (YRD) region of China. Understanding the relationship of O3 with its precursors and contributions of different sources in O3 formation is essential for the development of an O3 control strategy. This study analyzed O3 sensitivity to its precursors using a box model based on online observations of O3, non-methane hydrocarbons (NMHCs), nitrogen oxides (NOx), and carbon monoxide (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…However, they displayed completely different behavior toward O 3 variation (Figure 6g,h): HCHO was apparently higher for clusters 1 and 4 associated with evident O 3 production, while NO 2 was difficult to distinguish among them. This implied that the photochemical generation of O 3 was basically dominated by VOCs rather than NO x in Shanghai, which has also been reported in previous studies [41,42].…”
Section: Clustering Of O3 Diurnal Patternssupporting
confidence: 85%
“…However, they displayed completely different behavior toward O 3 variation (Figure 6g,h): HCHO was apparently higher for clusters 1 and 4 associated with evident O 3 production, while NO 2 was difficult to distinguish among them. This implied that the photochemical generation of O 3 was basically dominated by VOCs rather than NO x in Shanghai, which has also been reported in previous studies [41,42].…”
Section: Clustering Of O3 Diurnal Patternssupporting
confidence: 85%
“…For most of the newly-studied cites, urban areas were found in a VOC-limited regime, with two exceptions in Weinan and Nantong, both of which were in a mixed-limited regime [32,34]. However, transition from a VOClimited [35] to a mixed-limited O 3 formation regime [28] was indicated in some suburban areas of the YRD, mainly owing to decreases in NO x emissions in the recent years. As to altitude dependence, an analysis of airborne measurements in the NCP showed that O 3 formation became more sensitive to NO x emissions with increasing heights [36].…”
Section: O 3 Formation Regimementioning
confidence: 95%
“…Observation-based results from the past 5 years suggest that this situation has largely remained despite decrease in NO x emissions and increase in VOC emissions, e.g. in urban areas of Shanghai [28], Nanjing [29], and Wuhan [30]. The recent studies have expanded to less-developed cities NMVOCs are the total mass of non-methane hydrocarbons and oxygenated VOCs.…”
Section: O 3 Formation Regimementioning
confidence: 99%
“…NO x can either promote O 3 production through photochemical reactions with atomic oxygen (O), O 2 , or mitigate O 3 formation by removing OH from the oxidation cycle. At the same time, ambient radical budget and weather conditions can also affect the O 3 generation regime (Li et al, 2019b;Liu and Wang, 2020a;Lin et al, 2020;Wang et al, 2020).…”
Section: Driving Factors Of Interannual Changes In O 3 From 2014 To 2020mentioning
confidence: 99%